Superb impact resistance of nano-precipitation-strengthened high-entropy alloys - Ao Fu; Bin Liu; Zezhou Li; Tao Yang; YuanKui Cao; Junyang He; Bingfeng Wang; Jia Li; Qihong Fang; Xingwang Cheng; Marc A. Meyers; Yong Liu (Advanced Powder Materials)
Critical engineering applications, such as landing gears and armor protection, require structural materials withstanding high strength and significant plastic deformation. Nanoprecipitate-strengthened high-entropy alloys (HEAs) are considered as promising candidates for structural applications due to their enhanced strength and exceptional work-hardening capability. Herein, we report a FeCoNiAlTi-type HEA that achieves ultrahigh gigapascal yield strength from quasi-static to dynamic loading conditions and superb resistance to adiabatic shear failure. This is accomplished by introducing high-density coherent L12 nanoprecipitates. Multiscale characterization and molecular dynamics simulation demonstrate that the L12 nanoprecipitates exhibit multiple functions during impact, not only as the dislocation barrier and the dislocation transmission medium, but also as energy-absorbing islands that disperse the stress spikes through order-to-disorder transition, which result in extraordinary impact resistance. These findings shed light on the development of novel impact-resistant metallic materials.